Structural Modeling of Object Relations Mediated by Cognitive Emotion Regulation to Predict the Love Trauma Syndrome in Female Students - Farzad Dehghanifar; Farshid Khosropour; Hassan Mohammad tehrani (Zanjan University of Medical Sciences and Health Services, 2020)
Background: Love trauma syndrome includes a set of symptoms manifesting after the end of an emotional relationship and negatively affecting performance in various areas. Objectives: The current study aimed at determining the effect of object relations mediated by cognitive emotion regulation on the prediction of love trauma syndrome in female students. Methods: The correlation-based structural equation modeling was employed as a research method. The statistical population included all female students in Kerman, Iran, in the academic year of 2019-20. A total of 243 subjects were selected by multi-stage cluster sampling. Data collection instruments included the Ross love trauma inventory (LTI), the Bell object relations and reality inventory (BORRTI), and cognitive emotion regulation questionnaire (CERQ). Data analysis was performed by the structural equation modeling using SPSS and LISREL software. Results: The study findings indicated that object relations directly affect the cognitive regulation of negative emotion; on the other hand, cognitive emotion regulation plays a mediating role between object relations and love trauma syndrome. According to the findings of the structural equation modeling, the Root Mean Square Error of Approximation was 0.037, and the model had a good fit. Conclusion: The present study findings indicated the mediating role of cognitive emotion regulation between object relations and love trauma syndrome. Hence, the mentioned variables can be considered in interpersonal, pedagogical, family, and therapeutic relationships.